The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physrevb.94.125312
|View full text |Cite
|
Sign up to set email alerts
|

Projected equations of motion approach to hybrid quantum/classical dynamics in dielectric-metal composites

Abstract: Grüning, M. (2016)We introduce a hybrid method for dielectric-metal composites that describes the dynamics of the metallic system classically whilst retaining a quantum description of the dielectric. The timedependent dipole moment of the classical system is mimicked by the introduction of projected equations of motion (PEOM) and the coupling between the two systems is achieved through an effective dipole-dipole interaction. To benchmark this method, we model a test system (semiconducting quantum dot-metal nan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The closeness of the steady-state population difference achieved for the polar and non-polar hybrid system allows one to justify the approximations made to reach Eq. (15).…”
Section: B Transient Results: Critical and Non-critical Slow-downmentioning
confidence: 99%
See 1 more Smart Citation
“…The closeness of the steady-state population difference achieved for the polar and non-polar hybrid system allows one to justify the approximations made to reach Eq. (15).…”
Section: B Transient Results: Critical and Non-critical Slow-downmentioning
confidence: 99%
“…1,2 A prototype system to observe these effects comprises a semiconductor quantum dot (QD) and a spherical MNP. Several interesting optical effects have been studied in this hybrid nanostructure, including Fano-type phenomena in absorption of energy, [3][4][5][6][7] controlled coherent population transfer and ultrafast switching, [8][9][10][11][12][13][14][15] gain without inversion, [16][17][18][19] controlled optical bistability, 20-23 strongly modified resonance fluorescence, 18,[24][25][26][27][28][29][30] and four-wave mixing, [31][32][33][34] as well as plasmon-enhanced difference-frequency generation, 35 second-harmonic generation, 36,37 terahertz emission, 38 and Kerr nonlinearity. 39 Besides on-chip nanoscale photonic nonlinear devices, the coupled QD-MNP system may also have important applications in quantum technology, 40,41 sensing, 42 and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…An active research topic within the field of quantum plasmonics [ 1 , 2 ] is the efficient population control of the exciton and biexciton states in semiconductor quantum dots (SQD) closely placed to metallic nanoparticles (MNP) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For these hybrid nanostructures the population dynamics is rather different compared to the case of a single SQD, since the presence of the MNP amplifies the external electric field and induces interaction between SQD excitons and localized surface plasmons [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For these hybrid nanostructures the population dynamics is rather different compared to the case of a single SQD, since the presence of the MNP amplifies the external electric field and induces interaction between SQD excitons and localized surface plasmons [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A great portion of studies in this area is devoted to population transfer between the ground and single exciton states of the SQD, using external fields and with the MNP present [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 12 , 13 , 14 , 16 ]. In many of these works it is reported that the MNP substantially modifies the period of Rabi oscillations between these states [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ], which can even be destroyed for specific SQD-MNP distances [ 4 , 5 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation